1999
DOI: 10.1111/j.1151-2916.1999.tb02208.x
|View full text |Cite
|
Sign up to set email alerts
|

Subcritical Crack Growth in a Phosphate Laser Glass

Abstract: The rate of subcritical crack growth in a metaphosphate Nd-doped laser glass was measured using the doublecleavage-drilled compression (DCDC) method. The crack velocity is reported as a function of stress intensity at temperatures ranging from 296 to 573 K and in nitrogen with water vapor pressures ranging from 40 Pa (0.3 mmHg) to 4.7 × 10 4 Pa (355 mmHg). The measured crack velocities follow region I, II, and III behavior similar to that reported for silicate glasses. A chemical and mass-transport-limited rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 17 publications
2
42
0
Order By: Relevance
“…The internal WSC is not the only mechanism to explain the direct bonding energy increase but it seems to play an important role in the mechanical evolution of the bonding interface. Moreover, as the WSC is even more efficient at high temperature, 13 this mechanism might be more and more efficient during the post bonding annealing. The bonding mechanism of Si/SiO 2 or SiO 2 /SiO 2 plasma bonding might then be the same as for the chemical bonding but at lower temperature thanks to the specific plasma sub-subsurface.…”
Section: Wsc and Direct Bonding Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…The internal WSC is not the only mechanism to explain the direct bonding energy increase but it seems to play an important role in the mechanical evolution of the bonding interface. Moreover, as the WSC is even more efficient at high temperature, 13 this mechanism might be more and more efficient during the post bonding annealing. The bonding mechanism of Si/SiO 2 or SiO 2 /SiO 2 plasma bonding might then be the same as for the chemical bonding but at lower temperature thanks to the specific plasma sub-subsurface.…”
Section: Wsc and Direct Bonding Mechanismmentioning
confidence: 99%
“…The water stress corrosion may help the surface asperities to deform in order to increase the bonding area and thus the bonding energy. Furthermore, as the water stress corrosion rate depends on the temperature, 13 it could also participate to the bonding energy evolution versus annealing temperature. The direct bonding mechanism * Electrochemical Society Student Member.…”
mentioning
confidence: 99%
“…In other materials, such a glass, it is often reported that the crack initiates at the crowns of the hole without the presence of a starter notch (Janssen 1974; Michalske and Fuller 1985;Crichton et al 1999), while in polymers such as PMMA, a starter notch is necessary to initiate cracking at the crowns. Various schemes were undertaken in an effort to initiate a stable crack.…”
Section: Methodsmentioning
confidence: 98%
“…To explore this question we used the direct cleavage double compression (DCDC) method to grow a matching pair of isolated fracture surfaces. [9,21] Surprisingly, unlike indentation fractures, very little FPL signal was observed on the fracture surfaces produced using the DCDC technique. The high damage threshold of the fractures produced using the DCDC method was similar to that of a fracture free polished surface.…”
Section: Discussionmentioning
confidence: 99%